The Effects of Different Fuels on Wear between Piston Ring and Cylinder. (23rd July 2014) - Cesur, İdris; Ayhan, Vezir; Parlak, Adnan; Savaş, Ömer; Aydin, Zafer
Abstract : In internal combustion engines, mechanical friction occurs between engine components in contact with each other, leading to wear and important loss of efficiency. Mechanical energy absorbed by piston ring-cylinder pair in piston engines accounts for the largest portion of efficiency losses due to mechanical friction. Different engine lubrication regimes significantly affect wear and friction. In addition to selection of compatible materials, improvement of operational conditions and the properties of lubricants and fuels are of great importance to minimize wear. This study investigated the effects of oil, diesel fuel, oil + diesel fuel, and two different biodiesel fuels (SOME: sunflower oil methyl ester and TSOME: tobacco seed oil methyl ester) as engine lubricants and their effects on wear in piston ring-cylinder pair. The tests were carried out at different engine speeds and loads. Minimum wear occurred when using engine oil as lubricant, and maximum wear occurred when using diesel fuel as lubricant. The use of SOME and TSOME lubricant resulted in half the amount of engine wear, on average, compared to diesel.